Design Considerations for Microchannel Systems in Neonatal Intravenous Care - Archana, T.; Nachammai, N.; Praveenkumar , S. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This study explores the nuanced design of a microchannel system with a reservoir for precise controlled drug delivery in the context of neonatal intravenous care. The microscale dimensions and intricacies of drug administration in neonatal patients necessitate a meticulous approach to ensure both efficacy and safety. Leveraging the capabilities of COMSOL Multiphysics, simulations were conducted to optimize the micro channel’s design, focusing on achieving precise flow rates conducive to neonatal drug administration. The primary objective was to establish a microchannel configuration that could reliably deliver a range of drug volumes, from 1 ml/hr to 10 ml/hr. The simulations utilized a constant velocity output of 45 x10-15 m/s, ensuring a consistent parameter for exploration. The resulting cross-sectional areas, widths, and heights of the microchannel were meticulously adjusted to achieve the desired flow rates while maintaining a width of 1 μm for simplicity. The presented table and graph encapsulate the key dimensions corresponding to various flow rates, providing a practical guide for researchers and engineers involved in microfluidic systems design. The findings hold particular significance in neonatal care, where controlled drug administration is critical for ensuring therapeutic efficacy while mitigating potential adverse effects. In conclusion, this research contributes to the evolving landscape of biomedical technology by offering insights into the precise design parameters required for microchannels with reservoirs in neonatal intravenous care. The study's outcomes provide a foundation for further advancements in tailored drug delivery methodologies, enhancing the potential for personalized and effective treatments in neonatal healthcare scenarios.